Hormone synthesizing activity and oxidative modification of proteins in peripheral placental cytotrophoblast iron anemia in pregnant women - Kostyuk V.М. (Морфологія, 2013)
A morphological study of placentas of 90 pregnant women with iron deficiency anemia of various degrees of severity, and 30 cases without anemia that in the control group. Forming groups studied placentas conducted using the International сclassification of diseases, X-revision, based on the recommendations of the WHO (1998), depending on the severity of anemia: I st. – Hb 110-91 g/l, II st. – Hb 90-71 g/l, III st. – Hb 70-51 g/l. In the study group did not include cases with inflammation in the placenta or the manifestation of infection during pregnancy, cases of diabetes in the mother, isoimmune conflict, abnormalities of the litter (extrahorial, with anomalies of the umbilical cord or membranes, placenta multiparticle), multiple pregnancy, fetal malformations. The results showed that iron deficiency anemia pregnant promotes strengthening processes of free radical oxidation of proteins in all structures except peripheral cytotrophoblast multi trophoblastic giant cells and small fusiform trophoblastic cells of the basal plate and is accompanied by a decrease in the concentration of placental lactogen in all cells peripheral cytotrophoblast.